Teddy is brave: caring & sharing - Krutop, Lee (Five Mile Pr Pty Ltd Australia, 2008)
In this story, Teddy the bear faces various challenges that test his courage, from exploring dark caves to helping friends in need. With each adventure, he learns that being brave isn$1 (Bt about being fearless, but about standing up for others and overcoming fears. Teddy$1 (Bs bravery inspires those around him, showing that true courage comes from the heart.s